Model-based evidence of deep-ocean heat uptake during surface-temperature hiatus periods - Meehl, Gerald A.; Arblaster, Julie M.; Fasullo, John T.; Hu, Aixue; Trenberth, Kevin E. (Nature climate change, 2011)
In some decades, such as 2000–2009, the observed globally averaged surface-temperature time series has shown a flat or slightly negative trend. A modelling study provides evidence that heat uptake by the deep ocean may cause these hiatus periods and may be linked to La Niña-like conditions. There have been decades, such as 2000–2009, when the observed globally averaged surface-temperature time series shows little increase or even a slightly negative trend 1 (a hiatus period). However, the observed energy imbalance at the top-of-atmosphere for this recent decade indicates that a net energy flux into the climate system of about 1 W m −2 (refs 2 , 3 ) should be producing warming somewhere in the system 4 , 5 . Here we analyse twenty-first-century climate-model simulations that maintain a consistent radiative imbalance at the top-of-atmosphere of about 1 W m −2 as observed for the past decade. Eight decades with a slightly negative global mean surface-temperature trend show that the ocean above 300 m takes up significantly less heat whereas the ocean below 300 m takes up significantly more, compared with non-hiatus decades. The model provides a plausible depiction of processes in the climate system causing the hiatus periods, and indicates that a hiatus period is a relatively common climate phenomenon and may be linked to La Niña-like conditions.